Interaktionen und Kommunikationen in Hochschullernwerkstätten Theorien, Praktiken, Utopien - Kihm, Pascal; Kelkel, Mareike; Peschel, Markus (Lernen und Studieren in Lernwerkstätten, 2023)
The core element in learning workshops and university learning workshops are the interaction and communication processes between teachers and learners. The aim of this volume is therefore to examine the multifaceted ""interactions and communications in university learning workshops"" from a theoretical perspective and with practical insights. The diverse contributions explore how different target groups and different actors (un)consciously shape their interactions and communications in higher education learning workshops and how they influence each other. In our opinion, a differentiation of the different roles and role functions that actors in the university learning workshop can take on and also change is particularly necessary for a sharpening of specific interaction patterns.